Board Activities and Performance of Firms Listed at the Nairobi Securities Exchange - Aluoch, Moses Odhiambo; Kaijage, Erasmus S.; Iraya, Cyrus; Ogutu, Martin (European Scientific Journal, ESJ, 2018)
This study sought to examine the relationships among board activities and performance of firms listed at the Nairobi Securities Exchange. This study used a census approach and a target population of the study comprised of all companies listed at the Nairobi Securities Exchange between 2002 and 2016. A total of sixty five (65) companies were listed at the Nairobi Securities Exchange as at 31st December 2016. The data on board activities and performance of firms were extracted from annual reports of the individuals firms. This study employed longitudinal descriptive research design to determine relationships amongst board activities and performance of firms. A panel data regression analysis was conducted using random effects model which allowed the companies to have a common mean value of the intercept to determine whether corporate governance influence firm performance. An increasing trend was observed in other board activities variables such board ownership, board meetings, board tools, board committees and number of committees meetings. The study findings on the other hand revealed reducing trend in board tenure and board remuneration of listed firms Kenya. This was inferred to indicate that listed firms in Kenya have been strengthening their corporate governance over the study period. Regression analysis indicated that board activities are insignificant predators of Return on Assets, However board tenure, committees meetings and board remuneration were found to have a positive but insignificant effect on Tobin’s Q among listed firms in Kenya. Board ownership board tools, board meetings and number board committees were found to have negatively affected the performance measured by Tobin’s Q in listed firms in Kenya. However, only board tools significantly affected the performance measured by Tobin’s Q. The study concluded that listed firms in Kenya adopted corporate governance practices as part of the requirements of the regulating authority which had not impact on the specific company’s performance. Based on the findings of this study, stakeholders of listed firms and regulating authority such as Capital Markets Authority may relook at the board activities policies of listed firms with the view revising the existing policies or formulating new and more progressive policies to ensure shareholder interests are protected. These policies may go a long way to ensure listed firms not only strengthened their board activities during poor performing seasons but rather clear systems and activities that provide a clear roadmap to guide board operations.